(untitled) (Journal of the College of Basic Education, 2022)
I started my research with an introduction in which I mentioned that the Imamis are the foremost Islamic schools of thought at all, and they have independent opinions that they derive from the Book and the Sunnah, and they may meet in some with the Ash’aris, and in others with the Mu’tazilites, and they are independent in many things from the two groups. Then I divided my research into five topics: In the first research, I shed light on the intellectual Mu’tazila principles, and their influence on the sermons and words of Imam Ali, peace be upon him, especially in the discussions of monotheism and justice.